EFEK ADITIF Bi2O3 TERHADAP MIKROSTRUKTUR DAN KOEFISIEN NON LINEAR VARISTOR ZnO. - Tambunan, Walfred; Malik, Usman (Edu Research, 2013)
The varistor ZnO has been made by using raw materials: ZnO(E-Merck) and additive 0 %, 2.5 %, 5%, 7.5%, and 10% wt.Bi2O3. The important property of varistor ZnO is coefficient ofnon linier () and it can give influence correlation betweencurrent I and voltage V. The mixing process of raw materialswas done by using magnetic stirrer and liquid acetone asmedia, and then was dried at 60oC, and also grinded untilpassing 400 meshes. Pellet was made by using pressing 50MPa, and fired at 1050oC with holding time 2 hours. Afterfiring, all samples are characterized, such as: measurement ofcoefficient of non linier (), and observation of microstructureby using Scanning Electron Microscope (SEM). The resultsshow that sample without additive has  less than 5 and thissample has not properties as varistor, but the highest value of is 64 for sample with additive 7.5% Bi2O3. The result ofphotos SEM shows that the increase of percentage of additiveBi2O3 can influence of formation grain boundary and grainsize. Where, value of coefficient of non linier () is depend onexisting of grain boundary and thickness of grain boundary.